A study of a nuclear hydrogen production demonstration plant - Chang, Jonghwa; Kim, Yong-Wan; Lee, Ki-Young; Lee, Young-Woo; Lee, Won Jae; Noh, Jae-Man; Kim, Min-Hwan; Lim, Hong-Sik; Shin, Young-Joon; Bae, Ki-Kwang; Jung, Kwang-Deog (KOREAN NUCLEAR SOC, 2007)
The current energy supply system is burdened by environmental and supply problems. The concept of a hydrogen economy has been actively discussed worldwide. KAERI has set up a plan to demonstrate massive production of hydrogen using a VHTR by the early 2020s. The technological gap to meet this goal was identified during the past few years. The hydrogen production process, a process heat exchanger, the efficiency of an US thermochemical cycle, the manufacturing of components, the analysis tools of VHTR, and a coated particle fuel are key areas that require urgent development. Candidate NHDD plant designs based on a 200 MWth VHTR core and US thermochemical process have been studied and some of analysis results are presented in this paper.
Keywords: FUEL-PARTICLES; REACTOR; HTGR